Explanted malignancies after lung transplantation: the University of Michigan experience. (25th July 2022) - Mondoñedo, Jarred R; Huang, Tao; Lin, Jules; Wakeam, Elliot
Abstract: The management of patients with an explanted malignancy after lung transplantation is not well understood. We reviewed our institutional experience and outcomes at a single academic medical centre between December 1997 and April 2021 for patients with malignancies of all histologic types identified on explant pathology. Primary lung cancers were reclassified using the 8th Edition TNM staging and the 2021 World Health Organization histologic classification of lung cancers. Of the 733 patients undergoing lung transplantation, 15 (2.05%) were found to have malignancy on the explanted lungs, including 6 (0.82%) primary lung cancers. Four patients were found to have early-stage lung cancers, while 2 patients had advanced-stage IV disease. Survival ranged from 0 to 109 months for the entire cohort with median 23.2 [49.9] months in those with primary lung cancers. There were 2 recurrences following explanted stage I (15 months) and stage IV (53 months) diseases. Other explant pathologies included carcinoid tumourlets in 6 patients, lymphoma in 2 and metastatic leiomyosarcoma in 1. In conclusion, explanted lung malignancies are an infrequent but significant finding on explant pathology. Further data are needed to better characterize and stratify this patient cohort. Abstract : Lung transplantation is an effective therapeutic modality for patients with end-stage pulmonary failure, commonly encountered as a result of chronic obstructive pulmonary disease or idiopathic pulmonary fibrosis.